Epigenetic analysis of WRKY Transcription Factor Genes in Salt Stressed Rice (Oryza sativa L.) plants - MERİÇ, SİNAN; AYAN, ALP; ATAK, ÇİMEN; ÇELİK, ÖZGE (Elsevier, 2018)
It is important for plants to survive when they are subjected to environmental stress factors under different combinations in nature. In such conditions, epigenetic modifications such as cytosine methylations have a regulatory role in adaptive responses to changing environment. WRKY transcription factor family is one of the largest families managing regulation of various processes in plants. Although, the WRKYs are known to play important regulatory role in stress tolerance, the exact mechanisms underlying for regulation of each member under different conditions are not clarrified yet. Among WRKY family members, WRKY50 and WRKY72 were reported to be differentially regulated under salt stress. In this study, we compared the level of cytosin methylation patterns of both WRKY transcription factors under different salt concentration treated Osmancık-97 rice variety (Oryza sativa L.) seedlings. DNA methylation status of both genes in leaf tissues of NaCl stressed (0, 30 mM, 90 mM, 150 mM and 210 mM) rice plants were assessed by bisulfite sequencing. The sequencing reads were mapped according to Oryza sativa genome (v.7). Principal Component Analysis and the Fisher’s exact test were performed to compare the levels of methylated cytosines in CpG in the samples. Differentially methylated cytosines were identified and comparatively analyzed by methylKit. A total of 155 MetCs positions in the CpG context were detected comparing all libraries. 72 methylated cytosines correspond to WRKY50 sequence and 83 methylated cytosines were detected in the WRKY72 region. The methylation levels of the WRKY genes were found in negative correlation with gene expression at 90 and 150 mM NaCl treatments, however at 210 mM concentration the data indicate more complex status of the relation.